Paradigma Penafsiran Alegoris Surga Dalam Tafsir Indonesia-Kontemporer: Kajian Atas Tafsir Al-Misbah Karya M. Quraish Shihab - Wendi Parwanto (Ushuluddin Faculty, PTIQ Institute, 2022)
This study is motivated by the lack of studies that explain the interpretation shift on the theological-metaphysical verses in the Qur'an, including verses about heaven combined with a philosophical theoretical approach. Therefore, the researcher is interested in studying this theme further. This study explains the paradigm shift in the interpretation of heaven illustration in the Indonesian interpretation, namely M. Quraish Shihab. The theory used is the paradigm shift theory introduced by Thomas Kuhn. The conclusion of this article shows that there is a shift in the meaning of the illustration of heaven in each generation of interpretation in Indonesia, namely on the themes 1) The area of ??heaven; 2) The river that flows under heaven ; 3) Fruits in heaven; 4) Couples and nymphs in heaven; and 5) Green color and adornment for humans in heaven. In understanding these themes, M. Quraish Shihab tends to be rationalist and contextualist according to the current context. The thoughts that motivate his interpretive arguments are inseparable from the historicity of his life experiences, such as his intellectual career, organizational experience, teachers and the people of Indonesia as the targets of his interpretations. So all of that becomes a regulation and panoptiation in shaping his intellectual reasoning, including in the interpretation of the verses that illustrate heaven.